3D‐Printed Radiopaque Bioresorbable Stents to Improve Device Visualization. Issue 23 (17th October 2022) - Ding, Yonghui; Fu, Rao; Collins, Caralyn Paige; Yoda, Sarah‐Fatime; Sun, Cheng; Ameer, Guillermo A.
Abstract: Bioresorbable stents (BRS) hold great promise for the treatment of many life‐threatening luminal diseases. Tracking and monitoring of stents in vivo is critical for avoiding their malposition and inadequate expansion, which often leads to complications and stent failure. However, obtaining high X‐ray visibility of polymeric BRS has been challenging because of their intrinsic radiolucency. This study demonstrates the use of photopolymerization‐based 3D printing technique to fabricate radiopaque BRS by incorporating iodixanol, a clinical contrast agent, into a bioresorbable citrate‐based polymer ink. The successful volumetric dispersion of the iodixanol through the 3D‐printing process confers strong X‐ray visibility of the produced BRS. Following in vitro degradation, the 3D‐printed BRS embedded in chicken muscle maintains high X‐ray visibility for at least 4 weeks. Importantly, the 3D‐printed radiopaque BRS demonstrates good cytocompatibility and strong mechanical competence in crimping and expansion, which is essential for minimally invasive stent deployment. In addition, it is found that higher loading concentrations of iodixanol, e.g. 10 wt.%, results in more strut fractures in stent crimping and expansion. To conclude, this study introduces a facile strategy to fabricate radiopaque BRS through the incorporation of iodixanol in the 3D printing process, which could potentially increase the clinical success of BRS. Abstract : A radiopaque bioresorbable stent (BRS) is developed through the incorporation of a US FDA‐approved contrast agent, i.e. iodixanol, into a 3D‐printable, citrate‐based polymer ink. The 3D‐printed BRS demonstrates strong X‐ray visibility in chicken muscle tissues, mechanical competence during stent crimping and expansion procedures, and excellent in vitro biocompatibility.